MHD flow of longitudinal and torsional oscillations of a circular cylinder with suction in a couple stress fluid - Nagaraju, Gajjela; Ramana Murthy, Josyula (Zielona Góra: Uniwersytet Zielonogórski)
In this paper, we consider the flow an incompressible electrically conducting couple stress fluid generated by performing longitudinal and torsional oscillations of a porous circular cylinder subjected to constant suction/injection at the surface of the cylinder and in the presence of a radial magnetic field. A finite difference method is proposed to analyze the velocity components, in an infinite expansion of a couple stress fluid under vanishing couple stresses on the boundary. The effects of the magnetic parameter, couple stress parameter, Reynolds number, the ratio of couple stress viscosities parameter and suction parameter on velocity components and drag are discussed and shown graphically.
Keywords: longitudinal oscillations; torsional oscillations; drugs; suction; radial magnetic field